Applying Neutroalgebra and Neutrosophic Sentiment Analysis to Assess Last Mile Logistics Impact on Customer Experience - Rosa María Criollo Delgado; Julio Cesar Vidal Rischmoller; Sergio Marcelo Palomino Criollo (Neutrosophic Sets and Systems)
The aim of the paper entitled Neutrosophic Sentiment Assessment Using Neutroalgebra Applied to Last Mile Impact on Customer Experience explains the assessment of how factors related to last mile logistics impact customer perception. While there are many articles and research studies related to last mile logistics, the body of such articles simply focuses on repeating ordinary scope quantitative and qualitative analysis with an urban focus. This paper is intended to be an innovative contribution to the existing body of knowledge by ‘catching the wave’ of the current state of algebra and employing neutrosophy to develop a better understanding and modeling of customer emotions. The paper illustrates how combining advanced mathematics with sentiment analysis effectively identifies certain latent patterns in customers’ emotional experiences towards delivery services. As the authors point out, elements of time and content in everyday communication or delivery time and merchandise status have applications or operational efficiencies that extend beyond normal measurement.